Factors associated with teachers’ intention to leave their profession: teacher portraits from two European countries - Martinsone, Baiba; Rutkienė, Aušra; Žydžiūnaite, Vilma (Frontiers in Psychology, 2024)
Turnover of teachers is an important factor that impedes building and maintaining sustainable positive pedagogical practices to facilitate students' adjustment. The aim of this study was to elicit a portrait of teachers wanting to leave their profession. The research sample comprised 784 teachers from two European countries, namely 357 teachers from Latvia and 427 from Lithuania. Teachers were surveyed on their perceived stress, burnout, and intentions to leave their work alongside sociodemographic variables (age and work experience). It was found that although teachers in both countries reported moderate stress and burnout levels, Lithuanian teachers indicated higher levels of two burnout dimensions, namely exhaustion and inadequacy. However, Latvian teachers indicated significantly higher turnover intentions. The portrait of teachers who intended to leave their profession was different in both countries. An unexpected finding was that Latvian teachers with a higher desire to leave their profession indicated lower stress and burnout rates. They were mostly 45-64 years old and had more than 25 years of work experience. In Lithuania, teachers' intention to leave their work was reported by older and more experienced teachers experiencing higher stress and burnout. The findings highlight the need to consistently support the professional well-being of educators, both for committed teachers who want to stay in their profession and for those who might experience some detachment from their work at school.